Band Chemistry: Interpersonal and Group Dynamics in Rock Music - Baxter-Moore, Nick; Kitts, Thomas M. (Rock music studies, 2024)
The subject of band chemistry, or the interpersonal and collective dynamics within a rock band and their effects on longevity and musical creativity, has received little explicit scholarly attention. Drawing primarily on the words of musicians, this paper explores band chemistry in all its fragility and fickleness, easily disrupted and occasionally fortified by the ever-evolving interpersonal relationships of band members, commercial success or not, management and managerial change, producers, life on the road, drug and alcohol abuse, and the distribution of writing credits and royalties, among others. The paper argues that the intangible quality of band chemistry is most responsible, for good or bad, for the longevity of bands, and a major factor in their creativity while together.